Fabry disease: characterisation of the plasma proteome pre- and post-enzyme replacement therapy. Issue 11 (23rd August 2017) - Heo, Sun Hee; Kang, Eungu; Kim, Yoon-Myung; Go, Heounjeong; Kim, Kyung Yong; Jung, Jae Yong; Kang, Minji; Kim, Gu-Hwan; Kim, Jae-Min; Choi, In-Hee; Choi, Jin-Ho; Jung, Sung-Chul; et al.
Abstract : Background: Fabry disease is characterised by the progressive accumulation of globotriaosylceramide (Gb3) and related glycosphingolipids in vascular endothelial cells. Enzyme replacement therapy (ERT) clears this accumulation. We analysed plasma proteome profiles before and after ERT to characterise its molecular pathology. Methods: Two-dimensional electrophoresis and matrix-assisted laser desorption/ionisation-time of flight tandem mass spectrometry (MALDI-TOF MS) and tandem mass spectrometry (MS/MS) were done using plasma samples before and after ERT in eight patients with classical Fabry disease Results: After short-term ERT (4–12 months), the levels of 15 plasma proteins involved in inflammation, oxidative and ischaemic injury, or complement activation were reduced significantly. Among them, β-actin (ACTB), inactivated complement C3b (iC3b), and C4B were elevated significantly in pre-ERT Fabry disease plasma compared with control plasma. After longer-term ERT (46–96 months), iC3b levels gradually decreased, whereas the levels of other proteins varied. The gradual reduction of iC3b was comparable to that of Gb3 levels. In addition, iC3b increased significantly in pre-ERT Fabry disease mouse plasma, and C3 deposits were notable in renal tissues of pre-enzyme replacement therapy patients. Conclusion: These results indicated that C3-mediated complement activation might be altered in Fabry disease and ERT might promote its stabilisation.